Social Transfers as a Determinant of Intra-household Distribution: the case of Chile - Cuesta, José (Journal of Income Distribution®, 2004)
The effects of social transfers on individual participation and working hours are theoretically shown to differ for unitary and bargaining intra-household allocation models. This result is attributed to both the non-transferability of in-kind social transfers and differences in control of these transfers among household members. Using elasticities of social transfers on work effort (estimated through sample selection corrected participation probits and working hour OLS), new tests on intra-household allocation are developed for Chile. These tests strongly reject the unitary model and exogenous bargaining, accepting endogenous bargaining only among non-poor households. Poor households may use social incomes as investments for the future rather than for short-term strategic power relations.